(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2017)
Radio Frequency Identification (RFID) is a technology for automated identification of objects and people. RFID consists of the tags, one or more readers, and a backend database. RFID Tags are tuned to a particular frequency, and each tag has a unique ID. The communication between RFID tag and Reader implements wireless communication, which is considered risky and easily attacked. RFID protocol conquers a forward privacy problem but presumed that communication channel between reader and database is secure, which doesn’t agree with the real development of IOT. To conquer the privacy drawbacks of RFID protocol in mobile environment, an RFID security protocol based on the cryptographic hash function is design. This paper summarizes the problem about RFID security in the environment of IOT and suggests effective RFID security protocol based on cryptographic hash function. The suggested work will raise security to somewhat measure as well as denial of-service attack (DoS attack) and man-in-the-middle attack (MITM attack), while hold on to a reasonable computation cost.